A Novel Purine and Uric Metabolism Signature Predicting the Prognosis of Hepatocellular Carcinoma - Yang, Shengjie; Zhang, Baoying; Tan, Weijuan; Qi, Lu; Ma, Xiao; Wang, Xinghe (Frontiers in Genetics, 2022)
Background: Patients with hepatocellular carcinoma (HCC) often have abnormal purine and uric acid metabolism, but its relationship with prognosis is unclear. Methods: We collected the data of peripheral blood uric acid in 50 patients with HCC and analyzed the relationship with prognosis. At the same time, the transcriptome sequencing data of TCGA and GEO databases were collected to analyze the changes of purine metabolic pathway activity and construct a prognosis prediction model. Based on the prognosis prediction model related to purine metabolism, we further looked for the differences of immune microenvironment and molecular level, and provided possible drug targets. Results: We found that the level of serum uric acid was positively correlated with the prognosis of HCC. At the same time, purine metabolism and purine biosynthesis pathway activities were significantly activated in patients with poor prognosis of HCC. The prognosis prediction model of HCC based on purine metabolism and purine biosynthesis pathway can accurately evaluate the prognosis of patients with HCC. At the same time, we found that there were significant changes in tumor immune infiltration microenvironment and biological function at the molecular level in patients with over activation of purine metabolism and purine biosynthesis pathway. Conclusion: In this study, we found that the level of peripheral blood uric acid in patients with HCC is correlated with their prognosis. The prognosis of patients with HCC can be accurately predicted through the metabolic process of uric acid and purine.